Effect of dietary echium oil on growth, fatty acid composition and metabolism, gill prostaglandin production and macrophage activity in Atlantic cod (Gadus morhua L.) - Bell, J Gordon; Strachan, Fiona; Good, Joanne E; Tocher, Douglas R (Aquaculture Research, 2006)
Echium oil (EO) is a vegetable oil in which percentages of stearidonic acid (STA,18:4n-3) often exceed those of its n-6 series equivalent γ-linolenic acid (GLA, 18:3n-6). STA is elongated to 20:4n-3 in fish cell cultures, suggesting that EO could be included in diets for marine fish to increase tissue 20:4n-3 and 20:3n-6 and, thereby, modulate eicosanoid metabolism. Thus, the present study aimed to test the hypotheses that dietary EO would increase tissue 20:4n-3 and 20:3n-6 and modulate immune function and eicosanoid production in juvenile Atlantic cod (Gadus morhua L.) fed a diet where fish oil (FO) was replaced by EO. Duplicate groups of juvenile cod (initial weight ca. 4g) were fed for 18 weeks on fish meal based diets (55% protein and 16% lipid) that differed in oil source (FO or EO). There were no significant differences in growth and feed efficiency, hepato-somatic index, percentages of liver and flesh lipids and lipid class compositions for cod fed FO and EO. Percentages of 18:4n-3, 18:3n-6 and 20:3n-6 in the total lipids of flesh and liver were higher, and percentages of 20:5n-3 and 20:4n-6 were both lower in fish fed EO than in those given FO. In flesh, the increased 18:3n-6 and 18:4n-3 were primarily located in phosphatidylcholine and, to a lesser extent, phosphatidylethanolamine, whereas 20:3n-6 concentration was highest in phosphatidylinositol. Desaturation of 18:3n-3 (to tetraene products) and 20:5n-3 to 22:6n-3 in hepatocytes was very low but was increased by dietary EO. EO significantly decreased the production of prostaglandin F from gill cells stimulated with calcium ionophore A23187, and reduced head kidney macrophage activity, but had no effect on serum lysozyme activity or basic haematology. In conclusion, dietary EO may have beneficial effects on some immune parameters including eicosanoid metabolism in marine fish although this may be primarily due to decreased 20:4n-6 rather than increasing tissue levels of 20:3n-6 or 20:4n-3.